2019
DOI: 10.1002/jmri.26974
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Gd‐EOB‐DTPA‐Enhanced MRI for the Expression of Ki67 and Microvascular Density in Hepatocellular Carcinoma

Abstract: Contract grant sponsorNational Natural Science Foundation of China; Contract grant number: 81260214.BackgroundRecent studies have highlighted the diagnostic value of Gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA)‐enhanced MRI in small hepatocellular carcinoma (HCC). Ki67 and CD34 are histologic markers that reflect the proliferation of tumor cells and the microvascular density (MVD).PurposeTo explore the diagnostic value of Gd‐EOB‐DTPA‐enhanced MRI for Ki67 expression and MVD in HCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…We divided the 180 patients with HCC into 97 patients with low expression of Ki67 and 83 patients with high expression of Ki67 [a Ki67 < 20% was considered low expression and a Ki67 ≥ 20% was considered high expression (12)]. The two groups of patients were further divided into surgery and surgery + TACE sub-groups.…”
Section: Basic Information Of Patientsmentioning
confidence: 99%
“…We divided the 180 patients with HCC into 97 patients with low expression of Ki67 and 83 patients with high expression of Ki67 [a Ki67 < 20% was considered low expression and a Ki67 ≥ 20% was considered high expression (12)]. The two groups of patients were further divided into surgery and surgery + TACE sub-groups.…”
Section: Basic Information Of Patientsmentioning
confidence: 99%
“…Chen et al . reported that the SI value of tumors during the HBP in patients with HCC with a Ki67 index >50% was significantly lower than that in patients with a Ki67 index ≤50% 18 . In this study, the INI group showed significantly lower AFP levels and higher rates of patients with well‐differentiated HCC than the DI group.…”
Section: Discussionmentioning
confidence: 51%
“…The parameter K trans of free-breathing DCE-MRI using gadoxetic acid is reported to be highly associated with Ki67 proliferation status, and the lower value of K trans indicate higher Ki-67 indices and histological grades of HCC [103] . In addition, the T1 rt-20 min, tumor-to-muscle signal intensity ratio, ADC value and the arterial inhomogeneous enhancement pattern on gadoxetic acid-enhanced-MRI are also correlated with high-Ki-67 expression [104][105][106] . Furthermore, texture analysis, on the basis of gadoxetic acid-enhanced-MRI, can be applied as a tentative approach to preoperatively predict the Ki-67 status of HCC after curative resection [107] .…”
Section: Ki-67mentioning
confidence: 94%